A Concise Review on the Use of Mesenchymal Stem Cells in Cell Sheet-Based Tissue Engineering with Special Emphasis on Bone Tissue Regeneration - Yorukoglu, A. Cagdas (Stem Cells Int, 2017)
The integration of stem cell technology and cell sheet engineering improved the potential use of cell sheet products in regenerative medicine. This review will discuss the use of mesenchymal stem cells (MSCs) in cell sheet-based tissue engineering. Besides their adhesiveness to plastic surfaces and their extensive differentiation potential in vitro, MSCs are easily accessible, expandable in vitro with acceptable genomic stability, and few ethical issues. With all these advantages, they are extremely well suited for cell sheet-based tissue engineering. This review will focus on the use of MSC sheets in osteogenic tissue engineering. Potential application techniques with or without scaffolds and/or grafts will be discussed. Finally, the importance of osteogenic induction of these MSC sheets in orthopaedic applications will be demonstrated.